Biodiesel Production from Tung Oil in Laos PDR by Ultrasound-Assisted Transesterification - KEOMOUNLATH, Bounkhong; BOUNYAVONG , Sengthong; LATHDAVONG, Lemthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Tung oil is an emerging vegetable oil feedstock that has attracted growing attention for its potential conversion into biodiesel for energy applications. This research aims to investigate the biodiesel production process from sweet Vernicia montana seeds in Lao PDR. Biodiesel was synthesized via transesterification with methanol, wherein low-frequency ultrasonic irradiation (20 kHz, 130 W) was applied to enhance the reaction rate. This study also examined the physical properties of the produced biodiesel. In this study, biodiesel production was carried out using 1.3 wt% potassium hydroxide (KOH) as the catalyst. In this experiment, biodiesel production was carried out using oil-to-methanol molar ratios of 1:8, 1:10, and 1:12, respectively. The analysis results for oil-to-methanol mixing ratios of 1:8, 1:10, and 1:12 showed yield values of 79.92%, 87.52%, and 89.95%, respectively. The measured heat of combustion is very stable, approximately 45.5 kJ/kg. The viscosity varies with the mixing ratio, at 5.3, 4.89, and 4.5 cSt, respectively, and the flash point is constant, approximately 64 °C. From the experimental results, it can be concluded that biodiesel production from tung oil using ultrasonic-assisted transesterification yields satisfactory output and exhibits favorable physical properties. Therefore, tung oil has the potential to be an alternative raw material for biofuel production.